Across the stolen Ponds: The political geography of social welfare in rural eastern India. (October 2021) - Das, Ritanjan; Dey, Subhasish; Neogi, Ranjita
Highlights: Non-homogeneous political incentives are found to determine social welfare provisions in rural India. On ground distributive politics around welfare provision is shaped by innovative forms of clientelist transactions. Political alignment patterns within local governments are decisive in shaping distributive outcomes. Underlying social structures and practices can inhibit democratic decentralisation initiatives. Abstract: Despite a strong state and a slew of poverty reduction/welfare programmes, the provision of basic services to the rural poor in India remains puzzlingly inadequate. Moving away from the usual trend of aggregate welfare impact analysis that characterises most studies on this theme, we explore the on-ground distributive politics around the implementation of India's flagship social welfare programme, the National Rural Employment Guarantee Scheme (NREGS). Based on a mixed-method study in the state of West Bengal, using observational primary data and ethnographic material across 46 sample village councils ( gram panchayats ) from 2013 to 2018, we draw attention to the non-homogeneity in the way political incentives of welfare provision are orientated towards different parties and individual stakeholders. In doing so, we traverse across multiple domains of political economic concepts, particularly that of partisan alignment, clientelism and patronage, and unpack the differentiated constellation of localised political incentives founded on a unique form of transactional paradigm called settings. We show how these on-ground transactions provide a multitude of political incentives for ruling/opposition political parties and panchayat functionaries, often going beyond conventional ethno-favouritism ideas of patronage and assuming a more personalised context. In turn, we also argue that the idea of settings is useful in providing a deeper understanding of local state-society relations and the political geography of welfare provisions in rural eastern India.